Tantangan pendidikan agama Islam dalam menghadapi era society 5.0 - Afrilsyah, Ahmad Albert (Maliki Interdisciplinary Journal, 2024)
Islamic education is currently facing big challenges. After the Industrial Era 4.0, we were again surprised by the emergence of Society 5.0. Society 5.0 needs to be controlled and is a challenge for the world of Islamic education. This research formulates a case study of how Society 5.0 faces the challenges of Islamic education. This research uses a literature review. In "Data Collection Techniques", the author explores synchronous data by discussing the challenges of Islamic education in Society 5.0. Research Results: 1). Islamic education requires problem-solving abilities, critical thinking abilities, and creative abilities to answer the challenges of societal liberation in the 5.0 era. 2). Considering the Islamic education society in the 5.0 era, global education activities need to provide adequate resources such as teachers, lecturers and other educational resources.